Development of CBT Based Question Instruments Using WQC Application to Measure HOTS - Anggun Wulandari; Agus Suyatna; Viyanti Viyanti; Undang Rosidin (Jurnal Pembelajaran Fisika, 2021)
This study aims to develop an instrument for HOTS questions with the help of the Wondershare Quiz Creator application on Momentum and Impulse materials with design and material feasibility, suitable settings for HOTS questions with four types of HOTS questions, namely Multiple Choice, Multiple Responses, Sequence, and Matching. The research method used is Research and Development (R & D). This type of research is used to adapt the research design by Borg & Gall. The product development stages consist of research and data collection, planning, product development, product validation, product revision, and product results. The data collection technique used expert validation in developing HOTS questions based on CBT, then the data were analyzed quantitatively and descriptively. The analysis shows that the validity of the design has an average value of 4.21 with very high quality or validity and the validity of the material has an average value of 3.75 with high quality or valid. The highest scores for design and material validity were multiple responses 4.22 and 3.79. At the levels on C4, C5, and C6,  there is no difference in the validity and complexity of thinking caused by different types of questions.Keywords: CBT, HOTS, Momentum and Impulse, Wondershare quiz creator (WQC)DOI: http://dx.doi.org/10.23960/jpf.v9.n1.202110